The Influence of Constructionist Learning Environments on the Development of Global Citizenship Education Among K-12 Students: Constructionist Learning and Global Citizenship in K-12 (Constructionism Conference Proceedings, 2025)
While theoretical studies suggest that constructionist learning environments can cultivate skills essential to Global Citizenship Education (GCE), empirical research exploring this intersection is limited. This study investigates how constructionist learning environments impact the development of GCE among K-12 students. A qualitative research design, focusing on document analysis, was employed. A total of 177 student project reports generated over a one-year period during the 2023 academic year were collected. Trimester 1 included 51 projects (28.81%), Trimester 2 contained 53 projects (29.94%), and Trimester 3 encompassed 73 projects (41.24%). Through thematic analysis of the project titles, abstracts, and keywords, 150 representative codes were identified. The findings revealed that four distinct themes emerged: Environmental Sustainability, Technological Innovation, Social Responsibility, and Cultural Awareness. This study contributes to the growing body of research at the intersection of constructionism and GCE. By integrating constructionist methodologies into K-12 curricula, educators and policymakers can create transformative learning experiences that prepare students to act as informed and empathetic global citizens.